Does Teacher-Researcher Role Conflict Influence Psychological Well-Being Among the Lecturers? - Rafsanjani, Mohamad Arief; Pamungkas, Heni Purwa; Prakoso, Albrian Fiky; Sholikhah, Ni'matush (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2020)
The lecturer is a profession with two different functions: a teacher and a researcher. Teaching and research activities are inseparable and reciprocal and provide great benefit for lecturers. But, doing those activities simultaneously makes a high workload for the lecturer. This research employed the job demands-resources model to investigate the link between teacher-researcher role conflict and psychological well-being. This research was carried out on 250 lecturers in East Java, coming from three big cities, Surabaya, Malang, and Jember, taken by random sampling. Structural equation modelling was used to examine the research model. The results found that the teacher-researcher role conflict has a significant negative effect on work enthusiasm. On the contrary, the teacher-researcher role conflict has a significant positive effect on emotional exhaustion. These findings provide evidence to stakeholders (Universities and The Ministry of Education and Culture) to be more concerned about the dual role that lecturers must carry out as a teacher and a researcher.